Towards Coalition in a Multi-Agent Based Simulation for The Bomber Problem - Boutheina Jlifi; Zina Elguedria; Khaled Ghedira (IAES International Journal of Artificial Intelligence (IJ-AI), 2013)
The Bomber Problem BP can be considered as a discrete time model in which a bomber must survive for t epochs before reaching the target where it will drop its bombs. The Bomber problem is unsolved despite his appearance date since the 1960s. It is classified in the heading of research problems unsolved by Richard Weber. In fact, it can be classified as an NP-hard combinatorial optimization problem. Multi-agent simulation is for a long time privileged for modeling and experimentation of complex systems. This term includes concepts as diverse as strategic decision support or staff training. In this paper, we explore the challenge of simulating a system as complex as the Bomber problem with a MAS approach. Particularly, we demonstrate that Coalition forming in a MAS, models and simulates the collective resolution of the Bomber Problem within a dynamic agent organization in an efficient way. We illustrate our discussion with developed simulation results. DOI: http://dx.doi.org/10.11591/ij-ai.v2i4.2434